A Mountain Crossing Passport (過山榜) of the Iu Mien People: An Ethno-Textual Analysis - T. Daniel Arisawa; Chayanin Phansrisuwan (Journal of Integrative and Innovative Humanities)
This inquiry is anethno-textual critical analysis of a scroll Jiex Sen Borngv, a Chinese document that narrates the legend of the Iu Mien people. The document, also known as the Imperial Decree of Ping Huang, has been interpreted as a history, a fake, and an interethnic negotiation. The investigation proposes a fourth interpretation: the document contains an infiltration pejorative message. The study compares the scroll with three other manuscripts, examining their linguistic and cultural aspects. The aim is to make the document understandable to the Iu Mien, particularly the young ones who do not know Chinese. The study also hopes to stimulate a discussion on the Iu Mien’s ethnic identity, guided by Joshua A. Fishman’s questions: “Who are we?, From where do we come?, What is special about us?”.